Tytułowanie interlokutora w etykiecie staropolskiej na przykładzie "Szubienicznika" Jacka Piekary = Title of the interlocutor in the Old Polish etiquette on the example of "Szubienicznik" by Jacek Piekara - Kwiatkowski, Stanisław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study investigates addressative forms as etiquette on the example of expressions in "Szubienicznik" by Jacek Piekara. The location and time frame in which the action of a narrative takes place is Commonwealth of Poland in the 17th century. I analyze titles: waść, waćpan, asan and panie bracie. Lyrical character in accordance with realities of the described epoch they were named using the names of offices e.g. stolik, starosta, podczaszy, podsędek and podczaszowic. The author use formula dependent not only on who the recipient is, but also on intention of lirical heros.
Keywords: Piekara, Jacek (1965- ); tytułowanie; etykieta; szlachta polska; titles; etiquette; polish nobility